Analisis Kerentanan Lanskap Pesisir di Kecamatan Kuta Selatan, Bali - Fitriana, Devvy Alvionita; Gunawan, Andi; Munandar, Aris (Jurnal Arsitektur Lansekap; Vol.9, No.1, April 2023, 2023)
Vulnerability Analysis of Land Changes in Coastal Landscapes in Kuta Selatan District, Bali . Kuta Selatan District is a district located in the southern coastal part of Bali Province. Its existence in a coastal area makes this area rich in natural resources but also has a high level of vulnerability to damage, change, or disappearance of an ecosystem. This study aim to analyze the vulnerability of the landscape based on land cover changes in Kuta Selatan District and analyze the driving factors of landscape change. Land cover is classified into 4 (water bodies, vegetation areas, open areas, and built areas. Land cover change analysis used Landsat 7 ETM+ image data with test years 2000, 2010, and 2020. The spatial analysis method was used to analyze the land cover changes that occurred. The results showed that the rate of land cover change that occurs in Kuta Selatan District from 2000 to 2020 is 3-4% per year with dominated by increasing of open areas and built-up areas respectively. Meanwhile, the area of vegetation and water bodies has always experienced a decrease in area. This study also analyzes the driving factors of land cover change using the binary logistic regression analysis method. 7 variables are thought to affect changes in land cover that occur, namely distance to the main road (X1), distance to the river (X2), altitude/elevation (X3), slope (X4), population density (X5), distance from state universities (X6) and distance to tourist attractions (X7). The analysis results show that only the distance variable to the main road (X1) influences changes that occur in the 2000-2020 range. Supervision and policies that favor the sustainability of the existence of vegetation areas are the main focus of the recommendations.